STUDY OF THE REACTIONS OF FORMALDEHYDE WITH HYDROLYZABLE AND CONDENSED TANNINS OBTAINED FROM BARK EXTRACTS OF EUCALYPTUS CAMMALDULENSIS ALONG WITH THE DETERMINATION OF ADDED FORMALDEHYDE RATIO - Walid A. Kasir (Mesopotamia Journal of Agriculture)
The reactions of the hydrolysable tannin (Gallic acid) and condensed tannin (Flavanoid) with the released formaldehyde as a result of high temperature and different pH values along with different added ratios of para-formaldehyde were studied. According to the results obtained from Gel time and Pot life tests, the best values of pH and ratio of formaldehyde needed were determined, and they were 6.5 and 20% respectively. These values considered to be good enough to promote co-polymerization between the sites of tannins and those of formaldehyde to give suitable adhesive which can be used in manufacturing many wood products.